Developing Arabic Language Instructional Content in Canvas LMS for the Era and Post Covid-19 Pandemic - Moh. Fery Fauzi; Murdiono Murdiono; Irma Anindiati; Auqi Lu'lu In Nada; Rifqi Rohmanul Khakim; Lailatul Mauludiyah; I'anatut Thoifah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2020)
Online and offline learning practices must not ignore pedagogy, psychology, technology, instructional content, and other aspects of teaching and learning process. Instructional content needs more attention during and after Covid-19 pandemic because it must match the characteristics of students. Therefore, this problem has led to the development of mE-Book for Arabic learning in Canvas Learning Management System (LMS). This research aimed to investigate the effectiveness of mE-Book as instructional content for Arabic language learning in Canvas LMS and the extent of mE-Book acceptance by students in the framework of the Technology Acceptance Model (TAM) 3. This research used a nonrandomized control group pretest-posttest design by comparing two groups with and without mE-Book and the interview to know the students’ point of view about mE-Book. The results showed that mE-Book was effective as instructional content for Arabic language learning in Canvas LMS with large effect based on effect size criteria. Students’ perspectives showed that the use of mE-Book as instructional content for Arabic language learning in Canvas LMS is interesting for online and offline learning. In conclusion, students could accept mE-Book in learning activity in Canvas LMS because it eased students in Arabic language learning.